Magnetohydrodynamic effect on axisymmetric Stokes flow past a weakly permeable spheroid with a solid core - Prasad, M.K.; Bucha, T. (Archives of Mechanics, 2021)
The current research is focused on the creeping motion of fluid past a permeable spheroidal particle that has an impermeable core under the magnetic forces. Motion in the permeable zone is proposed to be regulated by Darcy’s law. At the fluid-porous interface, the continuity of the normal velocity component is assumed together with the balance of pressure with normal stresses and the Beavers–Joseph–Saffman–Jones (BJSJ) slip boundary condition. Vanishing of the normal component of velocity is used at the surface of the impermeable core. The drag on the spheroidal particle is obtained in an analytical form. The reliability of the drag coefficient on significant physical parameters such as permeability, non-sphericity parameter, Hartmann numbers, separation parameter (the measure of closeness between the porous particle and the core), and slip parameters is examined. Comparisons of results are made with the cases having no magnetic effect and show that the applied magnetic field possesses the ability to reduce the rate of flow of fluid. Well-known previously published results are deduced from the current analysis.